Antecedents to internet use to collaboratively consume apparel. Issue 4 (3rd October 2016) - Johnson, Kim K.P.; Mun, Jung Mee; Chae, Yoori
Abstract : Purpose: The purpose of this paper is to investigate attitude, subjective norm, perceived integrity of participants, materialism, and previous experience with collaborative consumption (CC) offline as antecedents to the CC of apparel facilitated by the internet. Design/methodology/approach: Survey research with convenience sample of consumers from within the USA. Findings: Attitude toward CC of apparel was significantly related to intention to collaboratively consume apparel online as was subjective norms. Previous experience with CC of apparel offline was significantly related to both attitude and behavioral intention. Perceived integrity of CC participants was related to previous experience with CC of apparel offline and attitude. Materialism was significantly and negatively related to previous experience with CC of apparel. Research limitations/implications: Research limitations include the use of a convenience sample of consumers and the research was limited to one form of CC. Practical implications: As a means to foster sustainable consumption, for those interested in promoting CC, consideration should be given to having existing participants of CC invite other family members and friends to try it as this might be more effective than targeting random members of the consuming public. Originality/value: An investigation of CC of a fashion item (apparel) that identifies predictors to participation.